Age as a prognostic modifier in anemic patients discharged after acute coronary syndrome. (3rd October 2022) - Cazorla-Morallon, D; Cordero, A; Tomas-Simon, F J; Sanchez-Munuera, S; Alvarez-Alvarez, B; Cid-Alvarez, B; Garcia-Acuna, J M; Rodriguez-Manero, M; Escribano, D; Bertomeu-Gonzalez, V; Zuazola, P; Gonzalez-Juanatey, J R
Abstract: Introduction: The presence of anemia on admission is a poor long-term prognostic factor in patients diagnosed with acute coronary syndrome (ACS). However, it is unknown whether age is a factor modifying the effect of anemia on mortality. Objective: To determine the effect of age on anemia in terms of long-term mortality in patients admitted for ACS. Methods: This is an observational study in which we included all patients discharged from cardiology for ACS in two centers from 2003 to 2020. Patients with anemia were classified by hemoglobin values <13 g/dL in men and <12 g/dL in women in the first blood count performed during hospitalization. The interaction between age and anemia was analyzed using the Cox regression model and the chunk test. We analyzed the effect of anemia on mortality using the Cox regression model adjusted for several confounding variables and the interaction with age. Results: We included 8872 patients diagnosed with ACS, with a mean age of 66.38 (SD ±12.76) years, 27.1% female and 34.3% diagnosed with ST-segment elevation ACS. The mean hemoglobin value was 13.88 (SD ±1.85) g/dL and 20.5% of patients were anemic on admission. During follow-up (median 1764 days, IQR 694–2439 days) there was an increased risk of all-cause mortality in patients with anemia adjusted for age and other risk factors (sex, renal function, GRACE score, atrial fibrillation, LVEF and previous revascularization), HR 15.5 (CI 5.77–41.75; p>0.005). We found a significant interaction between age and anemia (p<0.01). As represented in the figure, the adjusted risk of mortality decreased at older ages; in patients whose age was >80 anemia was not associated to higher mortality risk. Similar results were observed for cardiovascular mortality, HR 21.36 (CI 6.13–74.43, p>0.005). Conclusion: Age modifies the risk of mortality in patients discharged after an ACS being the risk of mortality higher in youngest ages and disappearing in octogenearians. There results should be taken under consideration for the treatment and management of ACS patients. Funding Acknowledgement: Type of funding sources: None.